2021
DOI: 10.31234/osf.io/uyhqa
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induced Negative Arousal Modulates the Speed of Visual Working Memory Consolidation

Abstract: This study examines how induced negative arousal influences the consolidation of fragile sensory inputs into durable working memory (WM) representations. Participants performed a visual WM change detection task with different amounts of encoding time manipulated by random pattern masks inserted at different levels of memory-and-mask Stimulus-Onset-Asynchrony (SOA). Prior to the WM task, negative or neutral emotion was induced using audio clips from the International Affective Digital Sounds (IADS). Pupillometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 107 publications
(174 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, negative emotion could also increase the efficiency of information processing (Eysenck et al, 2007;Xie, W., Sing, J. L. L., Martinez-Flores, A., & Zhang, 2021). As a result, memory items retained under the focus of attention in WM may be encoded with greater precision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, negative emotion could also increase the efficiency of information processing (Eysenck et al, 2007;Xie, W., Sing, J. L. L., Martinez-Flores, A., & Zhang, 2021). As a result, memory items retained under the focus of attention in WM may be encoded with greater precision.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the current study has revealed a potential moderator of the experimental effect of induced negative emotion on WM. Although the induction and assessment of emotional experiences have been extensively investigated in the past several decades (e.g., Bradley & Lang, 1994;Miers, Blöte, Sumter, Kallen, & Westenberg, 2011;Schubert, 2011;Siedlecka & Denson, 2019;Vuoskoski & Eerola, 2011), emotional experiences induced using laboratory stimuli and procedures can vary significantly due to individual differences in various factors such as emotion modulation and resilience (Chen et al, 2018;Quigley, Lindquist, & Barrett, 2014;Xie, W., Sing, J. L. L., Martinez-Flores, A., & Zhang, 2021;Xie, Cappiello, et al, 2018). Besides implementing more effective emotion induction procedures (Quigley et al, 2014), another essential step is to assess how the strength or intensity of induced emotional experiences across participants could modulate our experimental observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A linear interpolation was applied to the rest of the trials with blinks. Trials composed of more than 50% interpolated area within the analysis time window were then further excluded in the final analysis (33)(34)(35). In addition, we also excluded fast response time trials, where participants responded within 100 ms after probe onset (mean response time = 661 ms), and pupil analyses were only applied to the trials with correct response on the word valence evaluation task.…”
Section: Apparatusmentioning
confidence: 99%